Promoting the Conduct of Medical Education Journal Clubs in Teaching Medical Institutions - Shrivastava, Saurabh R.; Shrivastava, Prateek S. (Avicenna Journal of Medicine, 2021)
Background A critical appraisal of a research article as a part of journal club sessions is an essential aspect of postgraduate training across different medical institutions in varied settings. The purpose of the current review was to explore the merits of medical education journal clubs and identify the potential factors that need to be considered for conducting these journal clubs in medical institutions.Methods An extensive search of all materials related to the topic was performed in the PubMed search engine and a total of 51 studies were included in the review based on the suitability with the current review objectives. Keywords used in the search include medical education journal clubs in the title only (viz., journal club [ti] AND medical education [ti]; medical education journal clubs [ti]; journal club [ti]). The articles published in English language only were included in the review.Results Regardless of the extensive employment of the journal clubs in different medical specialties, it is quite alarming to note that not many institutions conduct journal clubs targeting the field of medical education. These sessions offer a unique opportunity to the participants to assess the literature in a supportive fashion and play a defining role in ensuring better quality health care teachings to the medical students. However, we must understand that the successful conduct of medical education journal clubs requires specific considerations and groundwork, so that the students may benefit.Conclusion In conclusion, the medical education journal clubs have not been frequently conducted, as more preference has been given to the subject-specialty journal clubs. However, considering the scope and benefits that journal clubs add to improve teaching, all medical institutions should advocate to conduct medical education journal clubs within their premises in a structured manner.
Keywords: journal club; critical appraisal; medical education